2010
DOI: 10.1136/emj.2008.068635
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic utility of troponin estimation in patients presenting with syncope: a prospective cohort study

Abstract: AMI is infrequent (1.4%), and estimation of troponin I provides little additional benefit to the presenting ED ECG in identifying patients with syncope due to AMI. Troponin I should not be used to rule out AMI in adult patients presenting with isolated syncope. Troponin I may predict 1-month serious outcome or all-cause death in syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…31 Similar findings were not reported in the two remaining studies that looked at the outcome measure of other serious AEs. 31 Similar findings were not reported in the two remaining studies that looked at the outcome measure of other serious AEs.…”
Section: Other Serious Aessupporting
confidence: 70%
See 1 more Smart Citation
“…31 Similar findings were not reported in the two remaining studies that looked at the outcome measure of other serious AEs. 31 Similar findings were not reported in the two remaining studies that looked at the outcome measure of other serious AEs.…”
Section: Other Serious Aessupporting
confidence: 70%
“…Significant statistical heterogeneity among studies was observed (χ 2 = 2250.74; P < 0.001), with 99.7% of variation in estimated size attributable to differences in study characteristics (I 2 = 99.7). Reed et al 31 noted the mean age was higher in those who had troponin measured (74 AE 14 vs 68 AE 18 years, P = 0.018).…”
Section: Proportion Of Troponins Measuredmentioning
confidence: 96%
“…Almost 20% of patients had troponin concentrations above our institution's current diagnostic threshold of 0.05 ng/ml for myocardial infarction. Yet only 2% of patients were diagnosed with myocardial infarction in our original study where a higher diagnostic threshold of 0.20 ng/ml was in use 1. We found that in patients with syncope, any increase in troponin concentration was associated with increasing risk of serious outcome and death at both 1 month and 1 year, even at very low levels of troponin.…”
Section: Discussionmentioning
confidence: 64%
“…Our group has already reported that plasma troponin concentration may predict 1-month serious outcome or all-cause death in syncope1 in a cohort of 289 patients enrolled into the ROSE study 2. These patients were admitted during the validation of a contemporary sensitive troponin I assay in our institution 3.…”
Section: Introductionmentioning
confidence: 99%
“…Troponin is not required to rule out acute coronary syndrome (ACS) or myocardial infarction (MI) unless the ECG shows changes consistent with acute ischaemia 45. While high sensitivity troponin does have prognostic ability (ie, it can predict short-term (1 month) and long-term (1 year) risk of serious outcome and death),46 47 it is not practice changing in clinical practice as yet and should presently only be measured if ACS or MI is suspected.…”
Section: When Is a Troponin To Rule Out Acute Coronary Syndrome Requimentioning
confidence: 99%